Psychological training of employees of socio-psychological services to act in extreme situations official activity - Тамара Кушнірова; Марина Чичуга (Київський національний університет імені Тараса Шевченка, 2015)
The article analyzes the basic concepts of psychological readiness of employees of law enforcement agencies to actions in extreme situations. Identified external and internal factors influencing psychological readiness of employees of the socio-psychological service of the institutions of execution of punishments to the actions in extreme situations official activity. The analysis of possible consequences of influence of profes- sional factors on the identity of the people of the institutions of execution of punishments. The structure of psychological readiness of employees of socio-psychological service for action in extreme situations, namely: intellectual, emotional-volitional, physiological, motivational, and communicative components. General principles and components of professional-psychological support of professional activities of personnel of the State criminal- Executive service of Ukraine.

В статті проаналізовано основні поняття психологічної готовності працівників правоохоронних органів до дій в екстремальних ситуаціях. Визначено зовнішні та внутрішні фактори, які впливають на психологічну готовність працівників СПС УВП до дій в екстремальних ситуаціях службової діяльності. Здійснено аналіз можливих наслідків впливу факторів професійної діяльності на особистість співробітників УВП. Розкрито структуру психологічної готовності працівників СПС до дій в екстремальних ситуаціях, а саме: інтелектуальний, емоційно-вольовий, психофізіологічний, мотиваційний та комунікативний компоненти. Визначено загальні принципи та складові системи професійно-психологічного забезпечення службової діяльності працівників Державної кримінально-виконавчої служби України.
Психологічна підготовка працівників соціально-психологічної служби установ виконання покарань до дій в екстремальних ситуаціях службової діяльності
Keywords: психологічна готовність; екстремальні ситуації; психологічна підготовка; деструктивні психічні стани; psychological readiness; extreme situations; psychological preparation; destructive mental state